Analysis of Gadget Use and Gratification Among Students at Pondok Pesantren Sharif Hidayatullah Rejomulyo, Kediri City - Regga Ziyadatul Faricha; Prilani Prilani; Prima Ayu Rizqi Mahanani (Nusantara Society Lab, 2025)
The development of information technology in the 21st century has brought significant changes in various fields, including education and religion. The 2023 APJII report noted that more than 70% of Indonesian teenagers have internet access through gadgets, indicating that the younger generation lives in a digital era. This development also influences religious-based educational environments, one of which is Pondok Pesantren Sharif Hidayatullah Rejomulyo in Kediri City. This pesantren is categorized as a modern Islamic boarding school with a policy that allows students to bring and use gadgets outside of worship and Qur’anic study times. Such a phenomenon raises questions about the motives and gratifications of students in using gadgets. This study aims to understand the motives and gratifications obtained by students in using gadgets at Pondok Pesantren Sharif Hidayatullah Rejomulyo in Kediri City. The research applies a descriptive qualitative approach using observation, interviews, and documentation methods. The Uses and gratification theory is used as the analytical framework to identify cognitive, affective, personal integration, social integration, and diversion needs. The research informants consist of active students who use gadgets in their daily activities at the pesantren. The findings reveal that students use gadgets to seek academic information and current news, obtain entertainment, communicate with family and friends, express themselves, and relieve boredom. The gratifications gained align with the motives that correspond to the five categories of needs in the Uses and gratification theory.